Konsep Ulama Dalam Al-Qur’an: Kajian Tafsir Tematik Dan Analisis Linguistik Terhadap Makna, Kedudukan, Dan Relevansinya Di Era Modern - Ummu Fadhilah Imran Ibrahim; Sohrah; Rosmini (Jurnal Ilmu Agama Indonesia, 2026)
The point of departure for this research lies in the growing anxiety over the transformation of meaning and authority attached to the figure of the ulama in contemporary Muslim contexts, which are increasingly influenced by digital dynamics, the reconfiguration of values in modern life, and the widening gap in moral orientation. Within the present socio-cultural landscape, ulama are no longer perceived solely as custodians of religious knowledge and spirituality, but also as social actors who are compelled to respond to ethical, epistemological, and representational dilemmas. Accordingly, this study seeks to investigate how the Qur’an conceptualizes the notion of ulama by adopting a qualitative design grounded in library research, utilizing the methodological framework of thematic Qur’anic interpretation (tafsir maudhū‘ī) combined with semantic and linguistic analysis. The data set was compiled through a close and critical reading of Qur’anic passages, alongside classical and modern exegetical works as well as relevant academic studies, and was subsequently examined through a thematic lens to map out patterns of meaning and semantic linkages among the concepts of ‘ilm (knowledge), khasyiah (reverent consciousness), and hikmah (wisdom). The analysis yields three central thematic formulations. First, the Qur’anic portrait of ulama highlights individuals who harmonize intellectual reasoning with spiritual humility, thereby presenting an equilibrium between cognitive mastery and moral awareness. Second, the study identifies a growing tension between traditional scholarly authority and expanding popular visibility in the digital sphere, where markers of religious legitimacy tend to shift from profundity of knowledge toward public exposure and symbolic recognition. Third, the research uncovers indications of a moral degeneration among certain ulama figures, which underscores the urgency of redefining their function as moral guardians and agents of ethical and social responsibility within the Muslim ummah. Collectively, these results demonstrate that the Qur’anic conception of ulama should not be understood as a fixed status, but as a dynamic construct that interweaves intellectual, spiritual, and sociological dimensions. From a theoretical standpoint, this work contributes to the enrichment of thematic-linguistic approaches in Qur’anic exegesis and the sociology of Islamic scholarship; from a practical perspective, it provides reflective input for strengthening public ethics, advancing morally grounded Islamic education, and cultivating digital religious literacy in contemporary society.